2014
DOI: 10.2174/0929867321666140706130807
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Polyphenols and Type 2 Diabetes: Current Insights and Future Perspectives

Abstract: Significant evidence suggests that polyphenol-rich diets have the ability to protect against diabetes. Since several previous reviews focused on the nutrition and health effects including type 2 diabetes of polyphenols in 2007-2008, a number of related original publications have been pulished in this field. This review summarizes important advances related to influence of dietary polyphenols and polyphenol-rich diets on preventing and managing type 2 diabetes, as well as diabetes-mediated changes in bioactivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
185
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 308 publications
(210 citation statements)
references
References 0 publications
3
185
0
2
Order By: Relevance
“…Moreover, as previously mentioned, fat composition can substantially differ between studies, some using KD rich in unsaturated fatty acids and others rich in saturated fatty acids. Nevertheless, a recent systematic review and meta-analysis revealed that saturated fat intake was not associated with all-cause and cardiovascular mortality, coronary heart disease, ischemic stroke or type 2 diabetes, 141 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as previously mentioned, fat composition can substantially differ between studies, some using KD rich in unsaturated fatty acids and others rich in saturated fatty acids. Nevertheless, a recent systematic review and meta-analysis revealed that saturated fat intake was not associated with all-cause and cardiovascular mortality, coronary heart disease, ischemic stroke or type 2 diabetes, 141 …”
Section: Discussionmentioning
confidence: 99%
“…They can also inhibit α-amylases or α-glucosidases thereby cause a decrease in starch digestion [23]. Polyphenolics have been shown to exhibit both biological and pharmacological activities [6].…”
Section: Discussionmentioning
confidence: 99%
“…25 However, the low bioavailability of anthocyanins appears to be an obvious obstacle in achieving the desired beneficial effects (Xiao and Högger, 2015). Novel approaches for enhancing the bioavailability of these beneficial molecules in human bodies are desired to be developed.…”
Section: Accepted Manuscriptmentioning
confidence: 99%